2022
DOI: 10.1002/jmv.28098
|View full text |Cite|
|
Sign up to set email alerts
|

Disease severity and efficacy of homologous vaccination among patients infected with SARS‐CoV‐2 Delta or Omicron VOCs, compared to unvaccinated using main biomarkers

Abstract: From March 2021, various countries including Iraq issued prompted recommendations for increased COVID‐19 vaccine protection in individuals especially those at risk of catching the virus (i.e., lifestyle, health sector workers, and chronic diseases). It is critically important to understand the impact of COVID‐19 vaccinations with the most commonly used vaccines (Pfizer and AstraZeneca) among populations either on the severity of the disease or the transmissibility of SARS‐CoV‐2 variants of concern (VOCs) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 56 publications
1
19
0
1
Order By: Relevance
“…Furthermore, Omicron BA.1 was shown to be less pathogenic in vivo when compared to other VOCs ( 11 , 12 , 13 ) and less severe Covid-19 cases were reported in areas in which Omicron BA.1 was the dominating variant ( 11 , 14 , 15 , 16 , 17 ). Recent studies have confirmed the lower pathogenicity of BA.1, but less severe courses of Covid-19 are also due to the higher vaccination rate in the BA.1 wave compared to the Delta wave ( 18 ).…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, Omicron BA.1 was shown to be less pathogenic in vivo when compared to other VOCs ( 11 , 12 , 13 ) and less severe Covid-19 cases were reported in areas in which Omicron BA.1 was the dominating variant ( 11 , 14 , 15 , 16 , 17 ). Recent studies have confirmed the lower pathogenicity of BA.1, but less severe courses of Covid-19 are also due to the higher vaccination rate in the BA.1 wave compared to the Delta wave ( 18 ).…”
Section: Introductionmentioning
confidence: 95%
“…Coronavirus Disease 2019 (COVID- 19) is a worldwide pandemic with a high mortality rate. It is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1,2]. Patients infected with SARS-CoV-2 exhibit a broad variety of symptoms and disease progressions that are not solely due to their age or other health issues.…”
Section: Introductionmentioning
confidence: 99%
“…
We appreciate the interest in our article entitled "Disease severity and efficacy of homologous vaccination among patients infected with SARS-CoV-2 Delta or Omicron VOCs, compared to unvaccinated, using main biomarkers". 1 The commentors' comments were helpful in correcting a handful of typos in the article. However, our response aims to improve their understanding and widen their knowledge on the article.Comment 1: First of all, the article claimed that this is a "first molecular study" of covid-19 variants in Iraq.
…”
mentioning
confidence: 99%